Viable weed seed density and diversity in soil and crop productivity under conservation agriculture practices in rice-based cropping systems - Nandan, Rajiv; Singh, Vikram; Kumar, Virender; Singh, S.S.; Hazra, K.K.; Nath, C.P.; Malik, R.K.; Poonia, S.P. (Elsevier, 2020)
Viable weed seed density and diversity in soil were assessed in an experiment that comprised two types of crop rotation [rice-wheat and rice-maize], two crop residue management (without residue and with residue), and four tillage techniques: conventional tillage (CT) transplanted puddled rice (TPR) – CT wheat/maize (CTTPR-CT), unpuddled transplanted rice – zero tillage (ZT) wheat/maize (UPTPR-ZT), ZT transplanted rice (ZTTPR) – ZT wheat/maize (ZTTPR-ZT), and ZT dry seeded rice (ZTDSR) - ZT wheat/maize (ZTDSR-ZT). The aim was to investigate the density and community composition of viable weed seed in soil in UPTPR-ZT, ZTTPR-ZT, and ZTDSR-ZT systems with and without crop residue, using the seedling germination method. The soil seed density was assessed in 2013-14 and 2014-15 after 4th and 5th year crop cycles established on a sandy loam soil of Patna, India. Total viable seed density was the highest for Cyperus iria L. irrespective of the treatment in both years. Rice-wheat system recorded 4% higher (mean of two years) seed density over the rice-maize system. Residue management practices did not differ for total viable seed density in both years. The ZTDSR-ZT, UPTPR-ZT, and ZTDSR-ZT systems resulted in significantly higher Shannon-Wiener, Simpson, and evenness indices compared to the CTTPR-CT system. Total viable seed density was the lowest for ZTDSR-ZT compared to the remaining tillage practices in both years. The sequence for Leptochloa chinensis (L.) Nees emergence was ZTTPR-ZT > ZTDSR-ZT > UPTPR-ZT > CTTPR-CT in 2014-15 (P < 0.05), signifying the more dominance of monocotyledons in ZT systems. The density of total aboveground weed density (no. m−2) was higher in ZTDSR-ZT in 2013-14 and lower in 2014-15 compared with remaining tillage techniques at 65 days after sowing. Thus, higher aboveground weed density in ZTDSR-ZT system minimized the soil seed density over time. Complete ZT-based practices (ZTDSR–ZT, ZTTPR–ZT) with crop residue significantly enhanced the grain yield of component crops over the CTTPR–CT. Thus, it implies that exhaustion of soil seedbank in ZTDSR-ZT system after 5 years can reduce the aboveground weed infestation and attain the higher grain yield compared to the CTTPR-CT system.